Clinical Outcomes and Their Prognostic Factors among Cervical Cancer Patients with Bone Recurrence - Thiti Atjimakul; Jitti Hanprasertpong (Obstetrics and Gynecology International)
Background. Bone recurrence occurs in 0.75%-8% of cervical cancer patients after primary treatment. Only a few previous studies have reported on survival times associated with prognostic factors for bone recurrent cervical cancer. This study aimed to evaluate the oncological outcomes and their predictors among cervical cancer patients with bone recurrence. Methods. The medical records of cervical cancer patients with bone recurrence who received primary treatment at Songklanagarind Hospital from January 2002 to December 2017 were retrospectively reviewed. Prognostic factors were identified using a Cox regression model. Results. The study included 6,354 cervical cancer patients, of whom 98 (1.54%) had bone recurrence at a median time of 25 months after the primary treatment (range 4.9-136 months). The most frequent site of bone recurrence was the spine (81.00%); the two most common visceral coexisting recurrence sites were the lungs and the liver. The median recurrence-free interval (RFI) was 21 months. Of the patients with recurrence, 75 (76.50%) were treated with combined radiation therapy and chemotherapy. The one-year overall survival (OS) after recurrence was 22.70%. On multivariate analysis, age under 60 years at the time of recurrence diagnosis (hazard ratio [HR] = 2.48, 95% CI = 1.47-4.18, p=0.001) and an RFI less than 21 months (HR = 1.63, 95% CI = 1.04-2.55, p=0.03) were independent prognostic factors for OS after recurrence. Conclusion. Bone recurrence in cervical cancer patients is rare and is associated with poor survival. Our study found that age and RFI were significant prognostic factors for OS in cervical cancer patients with bone recurrence.